PENGEMBANGAN STRATEGIC COMPETENCE PADA KETRAMPILAN MEMBACA PEMBELAJAR BAHASA INGGRIS SEBAGAI BAHASA ASING MELALUI SELF REGULATED LEARNING - Dwi Winarsih; Farikah Farikah (Universitas PGRI Semarang, 2012)
The research aims to : 1) identify the development of learners’ strategiccompetence of in reading skill through self-regulated learning, 2) describe thedevelopment of learners’ strategic competence of in reading skill through self-regulated learning, 3) describe to what extend learners’ strategic competence of inreading skill through self-regulated learning.This research is categorized as classroom action research which implementstwo-time learning cycle. The subjects are the students of English Department, Facultyof Education and Teacher Training, Tidar University of Magelang. Questionnaire,observation and test of reading skill are used get the data.Self regulated learning which is implemented in each cycle enables thestudents to improve metacognitive strategy. It support the improvement of strategiccompetence as well, because this leaning technique activates students to learncollaboratively, improve students confidence and provide opportunity to the studentsto make use and relate their knowledge of language elements to the English textSelf-regulated learning also enables students to improve cognitive strategy inwhich students use analogy of their language element knowledge and social function,generic structure and lexicogrammatical feature knowledge of a text to comprehendthe meaning of words, phrases, clauses, and sentences. Thus, the improvement ofcognitive strategy which is reflected as the improvement of strategic competence goeshand in hand with the improvement of reading.